Concepções de extensão na comunidade Universitária da UFLA - Zouein, Georges Francisco Villela (2001)
This study had the objective of identifying and analyzing, in the Universidade Federal de Lavras - UFLA, the concepts and main factors that make it difficult or impede the execution ofuniversity extens.on activ.ties in the institution. For this, a case study was realized. Based on the hterary review, three analysis categories for the extension activities were created: Concepts with the objective or analyzing the academic communhys concept ofextens.on; Factors - with the objective ofraising the factors that the commun.ty pomts out as impeding; and, Characteristics - which could aggravate or attenuate the Factor's influence. The methodology that was used was based on the collect.on of quantitative data, through a survey, comprising an agreement/disagreement scale These data would be analyzed not only in adescriptive manner, but also interpreted from the point ofthe view ofthe four strata present tn the community - Professors, Employees, Undergraduate and Graduate students From he results, utilizing the method of the Likert summation in the analys.s of tte categories, it can be inferred that there is a theoret.c consensus about the activVs conceptions, except for the so called "Financiar *W ** understónds the extension as an opportunity to raise money), that was the most polemic category among the community. In relation tothe Factors and Characteristics there was not a consensus in the community, .nd.catmg that, although the theoretic speech about extension is assimilated by most, the community has many varied opinions, sometimes even «*>™^ *°* ** problems that make the activity difficult or impede its realization. Based on the answers the community was divided in four opinion groups denominated: Idealists (25 4%) - who defend the extension as one ofthe three most important functions of the university, without financial objectives and executed u,ia dialogic manner (Dialogicity is an important category raised by Freire (1980) about the presence of communication, dialogue, knowledge exchange, among the people involved in an extension activity). The members in this group have a commiLnt attitude and respect, allied to the defense of a publ.c and free university; Financial Defenders (28.4%) - also valorize the extens.on as one the basic functions ofthe university, however, they do not see aproblem in the financial levying through the activity, being divided in relation to the Dialogicity; Non-defenders (18%) - are apparently divided in two subgroups: one, less instructed, did not know how to answer most ofthe questions, therefor, does not know much about the subject; the other does not valorize the extension^ understands that it is less importam than the teaching and research, probably never discussed the Dialogicity, and, do not see a problem in the Financial conception; and Uncertain (22.4%) - who answered most ofthe questions in a contradictory manner or with central tendencies in the scale. The components of this group are confuse, don't know or are actually uncertain in relation to the importance of the activity, to how it should be executed, or about the financial objectives. At last, it can also be said that: the extension does not have, at UFLA, the same importance as the teaching and research activities, the community members, in general, are little involved with the activity ( more than 78% never practiced extension); they know and valorize the extension more through speeches, which they also reproduce, however, in practice, they present altitudes that not always are coherent with what is said or defended; and; the Dialogicity showed to be little known and/or considered by the academic community in its conceptions and practices of the activity.